Codeine‐related adverse drug reactions in children following tonsillectomy: A prospective study. (13th November 2013) - Prows, Cynthia A.; Zhang, Xue; Huth, Myra M.; Zhang, Kejian; Saldaña, Shannon N.; Daraiseh, Nancy M.; Esslinger, Hope R.; Freeman, Edita; Greinwald, John H.; Martin, Lisa J.; Sadhasivam, Senthilkumar
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To prospectively determine factors associated with codeine's adverse drug reactions (ADRs) at home in a large homogenous population of children undergoing outpatient tonsillectomy. Study Design Prospective, genotype blinded, observational study with a single group and repeated ADR measures documented by parents at home. Methods A total of 249 children 6 to 15 years of age scheduled for tonsillectomy were enrolled. The primary outcome was number of daily codeine‐related ADRs. We examined the number and type of ADR by race and by days and further modeled factors potentially associated with ADR risk in a subcohort of white children. Sedation following a dose of codeine was a secondary outcome measure. Parents recorded their children's daily ADRs and sedation scores during postoperative days (POD) 0 to 3 at home. Results Diaries were returned for 134 children, who were given codeine. A total of 106 (79%) reported at least one ADR. The most common ADRs were nausea, lightheadedness/dizziness for white children and nausea, and vomiting for African American children. In a subcohort of white children ≤ 45 kg, increased ADR risk was associated with the presence of one or more full function CYP2D6 alleles (P < 0.001), POD (P < 0.001), and sex (P = 0.027). Increased pain intensity (P = 0.009) and PODs 0 and 1 (P = 0.001) contributed to a higher sedation risk. Neither obstructive apnea nor predicted CYP2D6 phenotype were associated with sedation risk. Conclusions Our results provide evidence that multiple factors are associated with codeine‐related ADRs and support the FDA recommendation to avoid codeine's routine use following tonsillectomy in children. Level of Evidence 4. Laryngoscope, 124:1242–1250, 2014